(untitled) (Revista de Ciências Agroveterinárias, 2016)
The consumer market’s demand and requirement for wheat grains which present a satisfactory industrial quality have driven the demand for enhanced cropping systems, especially related to nutritional aspects. In this context, the purpose of this research was to evaluate how the sulfur supplementation and the usage of nitrogen (N) affect the baking quality and the yield of the wheat grain cultivar TBIO Itaipu®. A randomized block experimental design in factorial arrangement, with two sulfur managements (with and without) and four split nitrogen managements (I: 100% of N in the double ring; II: 30% of N in the tillering period + 40% of N in the double ring + 30% of N in the ear development; III: 50% of N in the tillering period + 50% of N in the double ring; IV: 50% of N in the double ring + 50% of N in the ear development period), arranged in four repetitions. Our results showed that the sulfur supplementation increased the gluten content, which has been positively correlated with the strength and extensibility of the bread dough. This had a positive influence on the technological parameters of the flour used for baking. The splitnitrogen fertilizer application (in double ring, tillering, and ear development) increased the wheat grain yield due to the greater number of tillers per plant and also of the wheat ears per square meter.